Avaliação da aptidão física de idosos atendidos em unidade de saúde da cidade de Fortaleza, Ceará - Cavalcante, Rossman Prudente (2005)
RATIONAL – Functional status is one of the key elements for the health of elderly people. Although Katz index is widely used scale for measuring functional status, its validity has not been assessed in the Brazilian context.Furthermore, detailed data on the functional status of elderly people attending secundary care health units in Brazil are not available. OBJECTIVES – the aims of this study were to describe the profile of the functional status and physical fitness of elderly patients attending secondary care health units in a Brazilian city; to assess the performance of the Katz index to screen for physical function impairment against objective tests to assess physical function (gold-standard). DESIGN/PARTICIPANTS – cross-sectional study among elderly patients attending a secundary care health unit in Brazil. RESULTS - 133 patients were enrolled (111 female, 22 male), the mean age of the sample was 71+ 6.5 years. The great majority (86.4%) was classified by the Katz index as functionally independent, but 47.3% were found with functional impairment when assessed by physical tests. There was no association between the scores of physical performance assessed by Katz index and those by the physical tests. The most critically impaired physical domains were aerobic endurance and flexibility of back muscles. The impairment of certain physical domains was associated with age and literacy. CONCLUSIONS – A high proportion of elderly patients attending a secondary care health unit showed physical function impairment, representing those who need physical intervention. In such setting Katz index is not a valid instrument to screen for physical impairment.